In Situ Derived Porous CoNi@Mo2C‑CNT Composites for Excellent Electromagnetic Wave Absorption Properties - Wen, Bo; Yang, Guorui; Wang, Yifan; Liu, Xiaofeng; Weng, Xianjun; Jing, Dengwei; Ding, Shujiang (Crystal growth & design, 2022)
To meet the requirement of intense electromagnetic wave absorption capacity, a rational electronic regulation mechanism of magnetic metals is implemented. In this work, the heterogeneous structures containing Mo2C, metal alloys, and carbon nanotubes were synthesized by the deposition and carbonization of melamine. In contrast to single metallic elemental regulation, the electronic structure of Mo2C is obviously shifted by bimetallic regulation, which results in strong polarization relaxation in the electromagnetic field. Herein, benefiting from the tunable electronic structure between the Mo2C and CoNi, the CoNi@Mo2C-CNT composites exhibited strong interfacial polarization loss at high frequencies as well as excellent electromagnetic wave absorption performance with an effective absorption bandwidth of 5.9 GHz (2.1 mm) and a minimum reflection loss of −49.7 dB. These results indicate that the metal and Mo2C heterostructure can be synthesized successfully and that the electronic binding adjustment enhances the interface polarization loss.